Recognize! : an anthology honoring and amplifying Black life - Hudson, Wade; Hudson, Cheryl Willis (Crown Books for Young Readers, 2021)
Contains a collection of poems, short stories, essays, historical excerpts, and artwork about the history, culture, and lives of Black Americans.